Diet selection at three spatial scales: Implications for conservation of an endangered Hawaiian tree snail. (14th September 2016) - Price, Melissa R.; O'Rorke, Richard; Amend, Anthony S.; Hadfield, Michael G.
Abstract: Several recent studies suggest local adaptation in multiple taxa across Hawaii's steep environmental gradients. Restoration efforts in devastated tropical island ecosystems may be deficient if we lack an understanding of the interactions and dependencies in communities that occur along these gradients. Endangered Hawaiian tree snails are part of a snail–epiphyte–plant system where they graze fungi and other microbes on the leaf surface, a process difficult to observe using conventional techniques. Tree snails have undergone catastrophic decline due to introduced predators, removal by shell collectors, and human‐influenced habitat degradation. Prior to this study, little was known about the relationship among tree‐snails, their host plants, and the epiphytic microbes on which they feed. In this study, we identified scale‐dependent selection of substrates in Achatinella sowerbyana and Achatinella lila across the species' ranges. We assessed: (1) within‐plant diet selection using high‐throughput DNA sequencing (micro‐scale); (2) among‐plant selection of tree host species (small‐scale); (3) and the influence of climate on this system (macro‐scale). Selection of substrates occurred at two scales: fungal communities in fecal samples differed in composition from those available on leaf surfaces; and at all sites, snail occurrence on Metrosideros polymorpha, a foundational forest plant, was significantly higher than expected based on availability. Habitat restoration efforts should focus on out‐planting of M. polymorpha, the preferred snail host tree, in degraded habitat. Fungal differences across sites suggest relocation efforts to predator‐free enclosures may be hindered by microbial shifts associated with geographic distance or differing environments.